Company and Brand Rebranding: A Study on the Electronic Retail Industry - Ilham Ramdana (COMMUNICATION MAJOR, 2022)
This study analyzes the rebranding process in the case of a brand change from White Brown Electronics to Informa Electronics. The method used is descriptive method with a qualitative approach. Sources of data obtained through library research and field studies in the form of observations and interviews. The research was conducted at Informa Electronics Lving World Alam Sutera in Tangerang City and the object of the research was how marketing communication strategies for electronic products at Informa Electronics. The data is analyzed through the data reduction or data sorting stage, then the data is presented or displayed, and finally concluded according to the research problem. The results show that Informa Electronics has succeeded in making people and customers believe and continue to shop at Informa Electronics. The conclusions obtained from the research are: Informa Electronics in the process of rebranding a brand involves various aspects, namely, benefit description, association, distinction, awareness or brand identity, brand image and create trust. Informa Electronics also uses various promotional media, both online and offline promotional media, to improve their marketing communication strategies. These various things were carried out in order to increase the knowledge of the public and customers about Informa Electronics so as to generate feedback, namely by buying electronic products at Informa Electronics. Informa Electronics also uses various promotional media, both online and offline promotional media, to improve their marketing communication strategies. These various things were carried out in order to increase the knowledge of the public and customers about Informa Electronics so as to generate feedback, namely by buying electronic products at Informa Electronics. Informa Electronics also uses various promotional media, both online and offline promotional media, to improve their marketing communication strategies. These various things were carried out in order to increase the knowledge of the public and customers about Informa Electronics so as to generate feedback, namely by buying electronic products at Informa Electronics.